Increases in best practice child restraint use among children aged 2–5 years in low socioeconomic areas after introduction of mandatory child restraint laws in NSW Australia. (7th October 2012) - Brown, J; Keay, L; Hunter, K; Bilston, L; Simpson, J; Ivers, R
Abstract : Background: In 2009 the Australian Road Rules were modified to specify use of age-appropriate restraints for children up to 7 years. Implementation of the new laws was expected to increase optimal restraint use, but international studies have reported little or no effect of legislation in low income and minority groups. Aims/Objectives/Purpose: To compare restraint practices in children aged 2–5 years in low socioeconomic areas of NSW before and after introduction of legislation specifying age-appropriate restraint use. Methods: Direct observations of children aged 2–5 years at sites within low socioeconomic areas were used to assess restraint practices. A pre-legislation sample was drawn from a 2008 cross-sectional observation survey (n=106) and post-legislation data were collected in 2010 from control sites in a cluster randomised trial (n=360). Logistic regression was used to compare restraint practices adjusting for variations in demographic distributions between the samples. Results/Outcome: Age-appropriate restraint use increased from 41% to 73%, and correct use from 34% to 47% in the post-legislation sample. After controlling for child's age, parental education, income and language spoken at home, the odds of children in the post-legislation sample being appropriately restrained were 2.2 times greater (95% CI 1.4 to 3.6) and the odds of them being correctly restrained were 1.6 times greater (95% CI 1.0 to 2.7) than children in the pre-legislation sample. Significance/Contribution to the Field: While there appears to have been an improvement in child restraint practices in low income populations following implementation of laws mandating age-appropriate restraint, the results indicate a need for further interventions to increase the number of children optimally restrained.